43 A novel role for small molecule glycomimetics in the protection against lipid-induced endothelial dysfunction. (17th November 2015) - Mahmoud, Ayman M; Wilkinson, Fiona L; Jones, Alan M; Wilkinson, James A; Romero, Miguel; Duarte, Juan; Alexander, M Yvonne
Abstract : Glycomimetics are molecules that mimic the structure of carbohydrates involved in important biological processes. Small molecule glycomimetics are an untapped source of novel therapies for endothelial dysfunction, a hallmark of cardiovascular complications associated with diabetes. The current study aims to investigate the possible protective effects of newly synthesised small molecule glycomimetics against lipid-induced endothelial dysfunction, with an emphasis on nitric oxide (NO) and induced oxidative stress. Glycomimetics were synthesised by the stepwise transformation of 2, 5-dihydroxybenzoic acid to a range of 2, 5-substituted benzoic acid derivatives incorporating the key sulfate groups to mimic the interactions of heparan sulfate. Acetylcholine-induced endothelium-dependent relaxation in mouse thoracic aortic rings was measured using wire myography, and human umbilical vein endothelial cells (HUVECs) function was assessed in the presence or absence of palmitate, with or without the test glycomimetics. NO and reactive oxygen species (ROS) production was measured using DAF-2 and H2DCF-DA, respectively. Colorimetric assays were used to determine lipid peroxidation and activity of the antioxidant enzymes. Expression of Akt, eNOS, Nrf-2, NQO-1 and HO-1 were assessed using RT-PCR and western blotting. At 1 µM concentration, the synthesised glycomimetics significantly improved endothelium-dependent relaxation ex vivo and protected HUVECs against palmitate-induced oxidative stress and reduced NO production. Pre-incubation of HUVECs with all compounds upregulated Akt/eNOS signalling, activated Nrf2/ARE pathway, and suppressed ROS-induced lipid peroxidation. In conclusion, our newly synthesised small molecule glycomimetics protect against lipid-induced endothelial dysfunction. These novel cytoprotective effects open the door to a new class of therapeutic drugs to target endothelial dysfunction.